Faecal sludge management practice in informal settlements of Bangladesh - Abu Towab Md. Shahriar; Kh. Mahfuz-ud- Darain (Center for Science and Technology, IAIN Surakarta, 2022)
Informal settlements suffer sanitation challenges of inadequate toilet facilities and a high accumulation rate of faecal sludge due to land crises and dense populations. However, settlement people who struggle with informal living, either way, manage to keep their toilets running. This research explores faecal sludge management practices by people in informal settlements. It took Notun-Bazar Char Khulna as a case, purposefully sampled toilets, and populations, and conducted interviews and group discussions among settlement people, sweepers, key persons, and detailed observations of settlement premises. It also mapped excreta flows and discharge locations in drawings and diagrams. It illustrates how faecal sludge from all types of containment ending in the water is unsafe. This study analytically finds practices related to periodical containment management, Collective emptying mechanism, and faecal sludge’s conditional conveyance available in the informal settlement. It suggests developing environmentally safe faecal sludge management in informal settlements with an appreciation of the identified practices.